(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To evaluate the effects of soft contact lens (SCL) use on the cytological status of the bulbar conjunctiva and tear film stability before and after transepithelial photorefractive keratectomy (TPRK) and to examine the association of these characteristics with postoperative healing processes. Material and Methods: This prospective comparative study included two clinical groups 30 patients (60 eyes) each: group 1 (patients who had not used SCLs) and group 2 (patients who had used SCLs for the most recent five years before surgery). All patients received transepithelial PRK [1]. The status of the ocular surface was assessed by impression cytology (Nelson’s classification grades 0-3) [2], Schirmer’s I test and non-invasive break-up time (NIBUT) before and 2 months after surgery. Severity of corneal opacity (haze) was assessed 2 months after surgery. Mann-Whitney test, Wilcoxon test, Fisher exact test and Spearman correlation were used for statistical analysis. Results: Preoperatively, the mean grade (standard deviation [SD]) of cytological changes was statistically significantly worse for group 2 than for group 1 (2.35 (0.66) versus 1.38 (0.69), p < 0.001). Two months after surgery, the mean grade (SD) of cytological changes in group 2 improved significantly (p = 0.003), but was still worse than that for group 1 (2.15 (0.61) versus 1.32 (0.54), p < 0.001). There was a moderate correlation of the grade of cytological changes at baseline with the severity of haze at 2 months (ρ = 0.47, p < 0.001). Additionally, the grade of cytological changes was mildly correlated with preoperative NIBUT (ρ = -0.20; p = 0.033) and two-month postoperative NIBUT (ρ = -0.18; p = 0.048). Conclusion: Long-term SCL use resulted in stable pathological changes in the ocular surface epithelium, which did not disappear completely two months after the cessation of CSL use and TPRK. Abnormal cytological status is a prognostic marker associated with the risk of postoperative haze.